Smart System for Monitoring and Controlling Harmful Gases in Avian Farming using IOT - Binisha, X.M.; Sharmila, J.; Umadevi, G.; Mathumitha, A. (Journal of ISMAC, 2024)
The poultry industry is vital for sustaining global food production, yet it faces challenges concerning environmental sustainability and animal welfare. Among these, management of ammonia (NH3) and carbon dioxide (CO2) gas emissions, temperature, humidity fluctuations, and dust control, are critical considerations. Current methodologies often lack real-time monitoring capabilities and effective mitigation efforts. To address these issues, this research proposes an IoT-based monitoring and control system tailored for poultry farms, focusing on managing and controlling gas emissions, temperature, humidity, dust, and light levels. Employing an ESP32 microcontroller and sensors such as MQ135 for NH3 and CO2 detection, DHT for temperature and humidity, and LDR for light intensity, the system ensures continuous monitoring and adjustment of environmental parameter. It monitors and controls the dust by managing the proper temperature and humidity to reduce the health issues in poultry and as well as regulates light by turning ON/OFF light during dark. The system activates ventilation when the gas exceeds its limit and sends alerts through GSM. By using Wi-Fi connectivity, remote monitoring through a Blynk app is facilitated, while data logging on Thing Speak enables comprehensive analysis. The system aims to control ventilation and prevent dust for better environmental conditions and poultry welfare.